κ-Carrageenan Enhances Lipopolysaccharide-Induced Interleukin-8 Secretion by Stimulating the Bcl10-NF-κB Pathway in HT-29 Cells and Aggravates C. freundii-Induced Inflammation in Mice - Wei Wu; Zhanghe Zhen; Tingting Niu; Xiaojuan Zhu; Yuli Gao; Jiangyan Yan; Yu Chen; Xiaojun Yan; Haimin Chen (Mediators of Inflammation)
Background. The dietary usage of carrageenan as common food additive has increased observably over the last 50 years. But there is substantial controversy about its safety. Methods. We investigated whether the κ-carrageenan could enhance lipopolysaccharide-induced IL-8 expression by studying its actions on the TLR4-NF-κB pathway. The aggravating effect of κ-carrageenan on Citrobacter freundii DBS100-induced intestinal inflammation was also investigated in a mouse model. Results. Our data show that κ-carrageenan pretreatment promoted LPS-induced IL-8 expression in HT-29 cells. Although CD14, MD-2, and TLR4 were upregulated, the binding of LPS was not enhanced. However, the pathway of Bcl10-NF-κB was triggered. Interestingly, κ-carrageenan competitively blocked the binding of FITC-LPS. Furthermore, pretreatment with κ-carrageenan for one week previous to gavage with C. freundii DBS100 markedly aggravated weight loss, mortality, and colonic damage. The secretion of cytokines was unbalanced and the ratio of Tregs was decreased significantly. In addition, κ-carrageenan, together with C. freundii DBS100, enhanced the transcription and secretion of TLR4 and NF-κB. Conclusions. κ-Carrageenan can synergistically activate LPS-induced inflammatory through the Bcl10-NF-κB pathway, as indicated by its aggravation of C. freundii DBS100-induced colitis in mice. General Significance. Our results suggest that κ-carrageenan serves as a potential inflammatory agent that magnifies existing intestinal inflammation.